Parole germaniche in bocca romana: Italia germanica sub specie LEI - SERGIO LUBELLO (Filologia Germanica)
After providing some terminological and methodological specifications, this paper focuses on common classifications and current repertories of Germanicisms in the Italian language and its dialects. The purpose of this study is to illustrate the materials included in the Lessico Etimologico Italiano [LEI]. Germanismi (edited by Elda Morlicchio; 5 fascicles published so far) and to provide a taxonomy which, starting from an etymological criterion, effectively enables the researcher to retrieve documentary materials which were not available in other repertories.